The relevance of relational capabilities in collaborative decisions. Issue 12 (7th October 2021) - Della Corte, Valentina; Aria, Massimo; Del Gaudio, Giovanna; Barney, Jay Brian; Cobanoglu, Cihan; Sepe, Fabiana
Abstract : Purpose: This study aims to focus on inter-firm collaboration, exploring the main capabilities that can make a business more or less open to collaboration; it also considers the role of both firm-specific and relationship-specific capabilities. The paper proposes a model that can be used to study how the combination of the two categories of capabilities determines a firm's approach to collaboration. Design/methodology/approach: Through a survey of high-end hotels in tourist destinations in Italy and the USA, this paper tests variable connected with firm-specific and relationship-specific aspects, using confirmatory factor analysis. Findings: Firms with greater capabilities are less open to cooperation; weaker firms with fewer resources appear to be more inclined to cooperate, probably to gain access to resources and competencies they do not possess. Research limitations/implications: From a scientific perspective, this paper suggests an analysis based on both individual and relational capabilities when deciding whether to collaborate, while most studies based on a relational view just consider relational capabilities. The study could be enlarged to other countries and contexts. Practical implications: From a practical perspective, it indicates the importance of accounting for different and sometimes diverging aspects when deciding to cooperate. Social implications: In terms of social implications, it shows that, apart from the relational capabilities they have, potential partners can decide not to collaborate. Originality/value: The paper suggests a method of analyzing both individual and relational capabilities when deciding whether to engage in a collaboration. It shows that firms' behavior does not necessarily depend on the firm's relational capabilities.